Transitioning Toward Sustainability: Advancing the Scientific Foundation: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
In 1999 the National Academies of Sciences, Engineering, and Medicine released a landmark report, Our Common Journey: A Transition toward Sustainability, which attempted to “reinvigorate the essential strategic connections between scientific research, technological development, and societies’ efforts to achieve environmentally sustainable improvements in human well-being.”1 The report emphasized the need for place-based and systems approaches to sustainability, proposed a research strategy for using scientific and technical knowledge to better inform the field, and highlighted a number of priorities for actions that could contribute to a sustainable future.
Keywords: Environment and Environmental Studies

Pathways to Urban Sustainability: Challenges and Opportunities for the United States - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Cities have experienced an unprecedented rate of growth in the last decade. More than half the world’s population lives in urban areas, with the U.S. percentage at 80 percent. Cities have captured more than 80 percent of the globe’s economic activity and offered social mobility and economic prosperity to millions by clustering creative, innovative, and educated individuals and organizations. Clustering populations, however, can compound both positive and negative conditions, with many modern urban areas experiencing growing inequality, debility, and environmental degradation.
Keywords: Environment and Environmental Studies

Underground Engineering for Sustainable Urban Development - National Research Council (The National Academies Press, 2013)
For thousands of years, the underground has provided humans refuge, useful resources, physical support for surface structures, and a place for spiritual or artistic expression. More recently, many urban services have been placed underground. Over this time, humans have rarely considered how underground space can contribute to or be engineered to maximize its contribution to the sustainability of society. As human activities begin to change the planet and population struggle to maintain satisfactory standards of living, placing new infrastructure and related facilities underground may be the most successful way to encourage or support the redirection of urban development into sustainable patterns. Well maintained, resilient, and adequately performing underground infrastructure, therefore, becomes an essential part of sustainability, but much remains to be learned about improving the sustainability of underground infrastructure itself. At the request of the National Science Foundation (NSF), the National Research Council (NRC) conducted a study to consider sustainable underground development in the urban environment, to identify research needed to maximize opportunities for using underground space, and to enhance understanding among the public and technical communities of the role of underground engineering in urban sustainability. Underground Engineering for Sustainable Urban Development explains the findings of researchers and practitioners with expertise in geotechnical engineering, underground design and construction, trenchless technologies, risk assessment, visualization techniques for geotechnical applications, sustainable infrastructure development, life cycle assessment, infrastructure policy and planning, and fire prevention, safety and ventilation in the underground. This report is intended to inform a future research track and will be of interest to a broad audience including those in the private and public sectors engaged in urban and facility planning and design, underground construction, and safety and security.
Keywords: Engineering and Technology

Airport Sustainability Practices - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's Airport Cooperative Research Program (ACRP) Synthesis 77: Airport Sustainability Practices compiles information about airport sustainability practices and adds them to the Sustainable Aviation Guidance Alliance (SAGA) website. The SAGA website was developed to assist airport operators in developing sustainability programs and provide guidance to those who have new data to input. The website contains entries on more than 900 sustainability practices that were developed by SAGA’s initial stakeholder group. However, a large percentage of these entries do not contain actual practice data.
Keywords: Transportation and Infrastructure

Transportation Systems for Livable Communities - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s Conference Proceedings on the Web 6: Transportation Systems for Livable Communities summarizes the results of an October 2010 conference that explored the challenges of incorporating livability into transportation programs and projects.The proceedings consist of presentation summaries from the opening sessions and panels, and summaries of key research needs and possible performance measures identified in the discussion groups.
Keywords: Transportation and Infrastructure

Guidebook for Incorporating Sustainability into Traditional Airport Projects - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s Airport Cooperative Research Program (ACRP) Report 80: Guidebook for Incorporating Sustainability into Traditional Airport Projects describes sustainability and its potential benefits, and identifies different applications of sustainable initiatives in traditional airport construction and everyday maintenance projects.The printed version of the report includes a CD-ROM that includes an airport sustainability assessment tool (ASAT) that complements the guidebook and may be used to assist in identifying sustainability initiatives that might be most applicable to an airport project. Through case studies, the tool also allows users to obtain more information about specific strategies and learn about sustainability initiatives that have been implemented in other airports. The case studies are also available for download in PDF format.The CD-ROM is also available for download from TRB’s website in two formats, either as an Excel file or an ISO image.Download the Excel file here.Links to the ISO image and instructions for burning a CD-ROM from an ISO image are provided below.Help on Burning an .ISO CD-ROM ImageDownload the .ISO CD-ROM Image(Warning: This is a large file and may take some time to download using a high-speed connection.)CD-ROM Disclaimer - This software is offered as is, without warranty or promise of support of any kind either expressed or implied. Under no circumstance will the National Academy of Sciences or the Transportation Research Board (collectively "TRB") be liable for any loss or damage caused by the installation or operation of this product. TRB makes no representation or warranty of any kind, expressed or implied, in fact or in law, including without limitation, the warranty of merchantability or the warranty of fitness for a particular purpose, and shall not in any case be liable for any consequential or special damages.
Keywords: Transportation and Infrastructure

A Debris Management Handbook for State and Local DOTs and Departments of Public Works - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 781: A Debris Management Handbook for State and Local DOTs and Departments of Public Works provides debris management practices for local, tribal, and state departments of transportation and for public works agencies. A PowerPoint presentation and a final report describing the methodology of the project are available online.
Keywords: Transportation and Infrastructure

Airport Sustainability Practices—Drivers and Outcomes for Small Commercial and General Aviation Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's Airport Cooperative Research Program (ACRP) Synthesis 69: Airport Sustainability Practices—Drivers and Outcomes for Small Commercial and General Aviation Airports explores drivers and outcomes of green initiatives undertaken at small commercial and general aviation airports. Drivers could include financial viability, staffing considerations, or other social or environmental factors.
Keywords: Transportation and Infrastructure

Sustainable Critical Infrastructure Systems: A Framework for Meeting 21st Century Imperatives: Report of a Workshop - National Research Council (The National Academies Press, 2009)
For the people of the United States, the 20th century was one of unprecedented population growth, economic development, and improved quality of life. The critical infrastructure systems-water, wastewater, power, transportation, and telecommunications-built in the 20th century have become so much a part of modern life that they are taken for granted. By 2030, 60 million more Americans will expect these systems to deliver essential services.
Keywords: Engineering and Technology; Earth Sciences